PEMANFAATAN MEDIA LEAFLET TERHADAP TINGKAT PENGETAHUAN PASIEN HIPERTENSI LANSIA DI POSYANDU LANSIA MELATI - Novia Ariani; Erna Prihandiwati; Hairulia Intan Wuri; Muhammad Ari Noor Apriawan (Jurnal Insan Farmasi Indonesia, 2023)
South Kalimantan Province has the highest prevalence rate in Indonesia, which is 44.13%. Data from the Banjarmasin Indah Health Center Report for 2021 shows that there are 1,161 cases of hypertension and have an elderly Posyandu with the highest disease of hypertension. Efforts to improve the health status of the elderly by increasing the knowledge of the elderly through the provision of drug information, one of which is through the media of leaflets. This study aims to determine the effectiveness of providing information on hypertension drugs using leaflets for elderly patients at the Posyandu Lansia Melati. The study used a quasi-experimental design with the one group pre and post test method. Data collection prospectively in March-April 2022 using a total sampling technique. Data analysis using the Wilcoxon test to see the effectiveness of providing drug information. The results showed the level of knowledge before being given drug information was in the good category at 23.22% and after being given drug information through leaflets there was a significant change with the good category at 100% (p <0.05). The conclusion of the study showed providing information on hypertension drugs using leaflets was effective in increasing the level of knowledge of hypertensive patients.